Opioid-Free Anesthesia (OFA) as a Safe Anesthetic Choice for Epilepsy Patient - Albertus Medianto Walujo; Dewa Ayu Mas Shintya Dewi; FX. Adinda Putra Pradhana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The opioid-free anesthesia (OFA) approach, although not widely employed in anesthesia, offers distinct benefits for some populations, such as epilepsy patients, due to the propensity of opioids to trigger seizures. Hence, the objective of this study was to conduct an opioid-free anesthesia (OFA) procedure on the left lateral rhinotomy in a patient with concurrent epilepsy. Case presentation: Our patient is a 59-year-old woman suffering from epilepsy with a left nasal cavity tumor, scheduled for a left midfacial degloving rhinotomy. Given the patient's epilepsy comorbid, we have opted for an opioid-free anesthesia (OFA) procedure. OFA procedures are not yet widely employed in anesthesia; however, they offer advantages for specific patient populations, including epilepsy patients, as opioids have the potential to induce seizures. Conclusion: The various OFA protocols being conducted worldwide require refinement, and the potential interactions of each component should be explored further.